Pharmacological or transcriptional inhibition of both HDAC1 and 2 leads to cell cycle blockage and apoptosis via p21Waf1/Cip1 and p19INK4d upregulation in hepatocellular carcinoma. (27th February 2018) - Zhou, Hengyu; Cai, Ying; Liu, Dina; Li, Menghui; Sha, Yu; Zhang, Wenlu; Wang, Kai; Gong, Jianping; Tang, Ni; Huang, Ailong; Xia, Jie
Abstract: Objectives: Histone deacetylases (HDACs) are commonly dysregulated in cancer and represent promising therapeutic targets. However, global HDAC inhibitors have shown limited efficacy in the treatment of solid tumours, including hepatocellular carcinoma (HCC). In this study, we investigated the therapeutic effect of selectively inhibiting HDAC1 and 2 in HCC. Methods: HDAC1 inhibitor Tacedinaline (CI994), HDAC2 inhibitor Santacruzamate A (CAY10683), HDAC1/2 common inhibitor Romidepsin (FK228) and global HDAC inhibitor Vorinostat (SAHA) were used to treat HCC cells. Cell cycle, apoptosis and the protein levels of CDKs and CDKNs were performed to evaluate HCC cell growth. Inhibition of HDAC1/2 by RNAi was further investigated. Results: Combined inhibition of HDAC1/2 led to HCC cell morphology changes, growth inhibition, cell cycle blockage and apoptosis in vitro and suppressed the growth of subcutaneous HCC xenograft tumours in vivo. p21 Waf1/Cip1 and p19 INK 4d, which play roles in cell cycle blockage and apoptosis induction, were upregulated. Inhibition of HDAC1/2 by siRNA further demonstrated that HDAC1 and 2 cooperate in blocking the cell cycle and inducing apoptosis via p19 INK 4d and p21 Waf1/Cip1 upregulation. Finally, H3K18, H3K56 and H4K12 in the p19 INK 4d and p21 Waf1/Cip1 promoter regions were found to be targets of HDAC1/2. Conclusions: Pharmacological or transcriptional inhibition of HDAC1/2 increases p19 INK 4d and p21 Waf1/Cip1 expression, decreases CDK expression and arrests HCC growth. These results indicated a potential pharmacological mechanism of selective HDAC1/2 inhibitors in HCC therapy.